"There's More to Frail than That": Older New Zealanders and Health Professionals Talk about Frailty. (1st December 2019) - Gee, Susan B.; Cheung, Gary; Bergler, Ulrich; Jamieson, Hamish
Abstract : There is general agreement that frailty is common and important in later life, but there is less agreement about what frailty is. Little is known about the extent to which practicing health professionals and older people hold a mutual understanding of frailty. Focus groups were held to engage older people and health professionals in discussion about what made them think that someone was frail. Eighteen older people took part across three focus groups, and se'venteen health professionals took part across another three focus groups. Both the health professionals and the older people talked about the experience of frailty as an interplay of physical, psychological, and social dimensions. Older people with frailty were seen as needing help and being vulnerable to adverse outcomes, but accepting help was positioned by older people as an adaptive choice. The experience of frailty was described as being mediated by the individual's psychological mindset, highlighting the importance of approaches that recognise strengths and resilience. A broader and more balanced understanding of frailty may help create more rounded and appropriate approaches to assessment and management.